Thin-film composite hollow fiber membranes for Pressure Retarded Osmosis (PRO) process with high power density - Chou, Shuren (2013)
For the first time, a specially designed pressure retarded osmosis (PRO) hollow fiber membrane has been successfully developed and applied in the PRO process to demonstrate its potential for power generation. The membrane fabrication method is similar to that used for making thin-film composite (TFC) forward osmosis hollow fiber membranes, but further optimization and improvement have led to a new type of TFC hollow fiber membranes with much greater mechanical strength in addition to its excellent separation property and high water flux.